Water supply sources in the neighborhood city of Lobo in Porto Velho – Rondônia, Southern Amazon - Menezes , Aline Caroline Oliveira; Zuffo , Catia Eliza (Seven Editora, 2023)
The objective of this work is to characterize the sources used to obtain water destined for residences in the Cidade do Lobo neighborhood in the city of Porto Velho, State of Rondônia - Southern Amazon. The methodology employed was descriptive, using the inductive method, and the procedures adopted consisted of bibliographical research, field verification, production and analysis of graphs and characterization of the water supply scenario in the neighborhood during the second half of 2018, through the application of a form with objective questions, in 58 residences, chosen by convenience sampling. It was possible to identify the predominance of two types of wells: the semi-artesian and the amazon, the latter as the main source of water supply for this population. The general network plays an important role in people’s lives, but the supply of treated water is limited to some homes in this neighborhood, forcing residents, who do not use well water for direct consumption, to seek alternative solutions to have access to better water. quality, including the purchase of water using a water tank or mineral water available in shops, in addition to collecting water using jerrycans in places that have piped water, demonstrating that a large part of the neighborhood’s population is excluded from policies offered by the government, regarding the supply of treated water through protected springs. DOI:https://doi.org/10.56238/globalhealthprespesc-010